Pengembangan Alat Bantu Hitung Gerak Vertikal Keatas Berbasis Graphical User Interface untuk Pembelajaran Fisika - Suherly, Tomy; Insani, Lyra Tri; Nasir, Muhammad (Jurnal Paedagogy, 2022)
This study aims to develop applications in the form of calculation and measurement tools on physical material, especially upper vertical motion. The research method used in this research is literature study and GUI (Graphical user interface) development research with a 4D approach (define, design, develop, disseminate). This development research has only reached the design and development stage, but has not yet reached the stage of user feedback. The results of this study indicate that the tool for calculating physics using a GUI (Graphical user interface) on vertical upward motion material based on Matlab can be used to calculate questions regarding vertical upward motion material correctly. All the menus contained in the GUI (Graphical user interface) for calculating tools can work properly and in accordance with the commands listed on the menu. The calculation tool designed can also be used as a physical calculator in solving Upper Vertical Motion (GVA) problems.